Ecosystem services in urban green areas: Contributions to the United Nations 2030 Agenda - Nascimento, Ana Paula Branco do; Santos, Silvia Rosana dos; Gaudereto, Guilherme; Gallardo, Amarilis Lucia Casteli Figueiredo (National Journal of City Management, 2022)
Urban green areas are spaces that contribute to the fulfillment of the Sustainable Development Goals (SDGs) established by the United Nations 2030 Agenda. These are spaces that can increase the offer of Ecosystem Services (SEs – Serviços Ecossistêmicos), which are essential to promote well-being and a healthy environment to humans. The objective of this study is the assessment of SEs offered by a green space located in São Paulo City. The Praça Alfredo Di Cunto, also known as Horta das Flores, was selected for this study. It is a public green space located in the Mooca Subprefecture, which is a region with a low green area index (2 to 5 m²/inhabitant). To assess the SEs offered by Horta das Flores, the methodology proposed by Gaudereto et al. (2018) named Índice de Serviços Ecossistêmicos para Áreas Verdes (ISEAV – Index of Ecosystem Services for Green Areas) was applied. We highlight the following results of our study: support SEs, represented by the vegetation cover and permeable areas, contribute to the achievement of goals SDG 6, SDG 13 and SDG 15; regulating SEs contribute to nutrient cycling, because litterfall is not removed; and provisioning SEs contribute to SDG 2, because Horta das Flores has a vegetable garden with food plants including unconventional ones. Horta das Flores offers many SEs, thus contributing not only to the quality of life of the regulars, but also to a more sustainable city and community (SDG 11), as it is a safe and inclusive green space.